Representations of the Commodification of the Carbon Market through Cartoon Art Using a Visual Metaphor Approach - Hidayatullah, Taufan (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2026)
The global climate crisis phenomenon has driven the transformation of the ecological function of forests into economic commodities through a carbon exchange mechanism that presents a paradoxical condition between nature conservation efforts and the demands of polluting industrial growth within the framework of sustainable development.. This study aims to analyze the representation of carbon trading as commodification through a visual metaphorical approach in caricature works. Methodologically, this study is an artistic research project that adopts the Art Consortium’s creation model through five systematic stages: preparation, elaboration, synthesis, concept realization, and evaluation. This creative process produces works that represent the commodification of the carbon market through visual metaphors. The analysis reveals that the use of visual metaphors simplifies the complex narrative of the green economy into provocative visual messages. The discussion highlights how each visual element functions as a critical tool against the commodification of nature, which is trapped within the interests of global capitalism. In conclusion, this artistic research affirms that caricature is not merely an aesthetic illustration but a medium that demands profound reflection on socio-environmental phenomena.